Implementasi Pelayanan Publik Berbasis E-Government Melalui Aplikasi SID (Sistem Informasi Desa) Di Desa Gading Watu Kecamatan Menganti Kabupaten Gresik - Yuliansyah, Al Ridho Saqi'an; arlupi utami, dian (Universitas Negeri Surabaya, 2024)
Implementation of e-government with the SID (Village Information System) application for the people of Grelsik Regency was also carried out to carry out public service activities at Desa Gading Watu. However, there are many delsa employees and some delsa people still do not understand the workings and mechanics of the SID application. This is due to socialization that is not evenly distributed and the community is not able to grasp the information explained by the village apparatus. In addition, there are still many people in Delsa Gading Watu who do not yet have a qualified device to be able to use the services of the SID application.The purpose of this research is to describe the Implementation of E-Government in the SID (Village Information System) application in Gading Watu Village, Menganti District, Gresik Regency. This research uses a qualitative model with descriptive research. The data sources used are primer and sekunder data. Data collection techniques used interviews, observations, and documentation. Data analysis techniques used in this research include four stages, namely data collection, data reduction, data analysis, and conclusion drawing. The results of this research show that (1) Government to Citizen/Government to Customer (G2C). In the implementation of SID (Desa Information System) in Desa Gading Watu faces several obstacles, there are people who are less agreeable and agreeable to this application. citizens who are less agreeable, namely there are still many desa people who are gaptelk. However, there are people who agree with the aim of making remote services easier. Government to Business (G2B). To facilitate the application of SID, sufficient socialization is (3) Government to Government (G2G). In implementing SID (Desa Information System) in Desa Gading Watu, it is necessary to coordinate and cooperate with several related agencies, one of which is Diskominfo Gresik City. (4) Government to Employees (G2E). Various efforts to improve the implementation of SID (Village Information System) in Gading Watu Village by improving the performance of employees who cannot use the SID application for the service process. If there are problems for employees or officials from other villages, the village apparatus helps to solve the problem. Keywords: Public Services, Implementation, E-Government